Effect of Fundamental Factors and Demographic Informations on Personality and Investment Decision - Ika Sisbintari; Suhadak Suhadak; Siti Ragil; Nila Firdausi Nuzula (Wacana Journal of Social and Humanity Studies, 2019)
Investment decision making is a process that involves investor psychology. Many events in capital market are anomalies that traditional finance cannot explain. Researchers in finance field then turn to non-economic aspects of investor psychology which causes behavioral finance to emerge. In principle, behavioral finance is a study of three fields of science, namely finance, psychology and sociology. This study aims to (1) test and explain the effect of fundamental factors on investment decision; (2) test and explain the effect of demographic informations on personality; (3) test and explain the effect of personality on investment decision; (4) test and explain the effect of demographic informations on investment decision. Data collection was carried out using a questionnaire with a response rate of 72.4% (of the 500 questionnaires sent, 362 returned questionnaires that could be analyzed). Data analysis used Generalized Structured Component Analysis (GeSCA). The results showed that (1) fundamental factors had a significant effect on investment decision; (2) demographic informations had a significant effect on personality; (3) personality had a significant effect on investment decision; (4) demographic informations had a significant effect on investment decision.